Market Share Analysis of Minimarkets and Grocery Stores in Palopo City - arsyad L; Megasari Megasari (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This study aims to determine the market share of Minimarkets and Grocery stores in Palopo city today as well as on the state of Equilibrium. The data analysis used in this study is Markov chain analysis. The Makrov process in this study is used to determine the selection of shopping places for future periods depending on the selection of shopping places in one previous period, as well as to forecast the rate at which a brand will gain or lose customers. In addition, Markov chains are also used to determine future equilibrium conditions. The results show the Market Share of shopping places in Palopo city today is as follows: Grocery stores (68%) then Indomaret (14%) and alfamart (10%). Next in line is Alfamidi (10.%), and finally other places (3%). In addition, the predicted market share of shopping places in Palopo city in the future is: Grocery stores (60%) then Indomaret (17%) and alfamart (8%). Next in line is Alfamidi (5.%), and finally other places (11%). The results of this research can be used by the government as a basis for making policies on permits for the establishment of minimarkets in Palopo City